Crime scene prevention and awareness level of the residents of brgy. Barayong Magsaysay, Davao del Sur - Abrea, Rogen Rey B.; Espina, Remar L.; Pejera, Ariel A. (--Davao del Sur: UM Bansalan College LIC, 2011)
This study is conducted to determine the crime scene preservation and awareness level of the residents of Brgy. Barayong, Magsaysay, Davao del Sur in terms of information dissemination, cooperation and protective measures. A total of six hundred sixty one (661) household as respondents of this study. The study found out that the most respondent is male that got a highest frequency of 358 or 54.2 percent. And most participants are belonging to the age of 20-29 percent. Most of them are Married which has the frequency of 430 or 65.1 percent, and most of them are Roman Catholic which has the frequency of 628 or 95 percent. The awareness level of the respondents in terms of information dissemination obtain a mean score of 5, interpreted as very high; cooperation obtain a mean score of 3.25, interpreted as moderate and protective measures obtain a mean score of 4, interpreted as high respectively. Based from the findings of the study, the researchers recommend that the government as well as the police organization should implement an effective programs and seminar to the residents of Brgy. Barayong, Magsaysay, Davao del Sur to enhance their knowledge in crime scene preservation and to make public participation more effective and also the chief administrator of a law enforcement agency must develop and enforce workable rules that will allow the crime scene to be preserved and allow the detectives and crime scene investigators to do their jobs properly.